Czynniki kształtujące zużycie czasu na produkcję rolną w gospodarstwach chłopskich (w świetle rachunku korelacyjnego) - Borowski, Stanisław (Wydział Prawa i Administracji UAM, 1966)
The purpose of the paper is to ascertain what part of the disposable time the vocationally active population devotes to agricultural production, what is the daily burden of that production and finally what kind of relation exists between that burden and the farm area. This information rests on source material obtained on the basis of direct observation in the peasant farms belonging to parents of the students of the Poznań School of Economics or else in the farms well known to the students. These observations were undertaken during 5 weeks in 1963, i. e. in the last week of February and in the first weeks of May, August, October and December. The farming persons and the permanently helping family members were included to the vocationally active persons. Among the latter group — a different treatment got the landladies. The whole disposable time of the vocationally active people was divided as follows: time devoted to agricultural production, to the household, to earning activities of non-agricultural character and finally to personal requirements. The people who devote most of their time to agricultural production are the farming persons, whereas the occasionally helping family members belong to the category of people spending least time on agricultural work. The time used in agricultural production is usually rising with the growing farm area. In the month of February, in farms up to 2 hectars the farming persons devoted daily to agricultural production 3,9 hours, the permamently helping family members 1,1 hour, in that category the landladies (1,1 hour. On the other hand in the farms of an area of 10—15 hectars, the above mentioned categories of persons devoted respectively 8,8, 3,8 3,5 hours. In the month of August in farms up to 2 hectars the farming persons devoted daily to agricultural production 6,3 hours, the permanently helping family members 5,6 hours, the landladies 5,7 hours. In the same month in the farms of an.area of 10—15 hectars were devoted respectively 12,8, 7,7, 7,9 hours. The coefficients of linear correlation between the time used in agricultural production and the farm area are positive and significant at the level of significance 0,05 for the farming persons, positive for the permanently helping family members, negative or positive but not significant for the landladies. The low level of correlation coefficients is due on the one hand to small samples and on the other hand to the phenomenon of earning money in nonagricultural occupations by some of the family members, then to the different degree of intensity in the plant production and different level of the animal stocks, different degree of mechanization and electrification of the farms.
Factors Determining the Consumption of Time Devoted to Agricultural Production in Peasant Farms according to Correlative Calculation